Efficient utilization of municipal solid waste incinerator bottom ash for autoclaved aerated concrete formulation - Liu, Yiquan (2023)
Contrary to the previous research on the general utilization of municipal solid waste (MSW) incineration bottom ash (IBA) in autoclaved aerated concrete (AAC), the given study strategically utilizes IBA for AAC formulation to improve IBA utilization efficiency and to enhance the hardened properties of the resulting IBA-AACs. A systematic classification and characterization approach was used to determine the suitable IBA fractions for each ingredient. The classified IBA with particle size less than 0.3 mm (IBA fines), IBA glass fraction (IBA-G), and coarse non-ferrous IBA with particle size greater than 1.18 mm (coarse IBA-ONF) were used as calcium, silica, and metallic aluminum (as an aerating agent) resource, respectively. The resulting IBA-AACs showed much higher specific strengths (about 40% enhancement) than the Control AAC due to the formation of relatively pure tobermorite gel. The leaching test results confirmed the safe utilization of AAC during and after the service life. The utilization of classified IBA optimized the amount of IBA that can be incorporated in AAC.